STRATEGI PENGEMBANGAN KETERAMPILAN KOMUNIKATIF DALAM MATA KULIAH AL-QURAN DAN HADIS PADA MAHASISWA BARU STAI AL-FURQAN MAKASSAR [STRATEGY OF DEVELOPING COMMUNICATIVE SKILLS IN THE COURSE OF AL-QURAN AND HADITH FOR NEW STUDENTS OF STAI AL-FURQAN MAKASSAR] - Ismail, Ismail; Putra, Amanda; Ramdani, Achmad Fadil; Amalia, Reski; Bahri, Tiara; Isna, Andi Nur; Karadona, Rosika Indri (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
Communication skills are a crucial element in the learning process, particularly in the subjects of Qur'an and Hadith, which emphasize not only cognitive aspects but also the internalization of spiritual and moral values.This study aims to examine strategies for developing communication skills in the teaching of Qur'an and Hadith among first-year students at STAI Al-Furqan Makassar. This research employs a descriptive qualitative approach using a literature review method. Data were collected through the analysis of various relevant sources, including books, journal articles, and previous studies discussing communication in Islamic education. The results indicate that active learning strategies such as group discussions, question-and-answer sessions, presentations, role-playing, the use of digital media, and peer teaching are effective in enhancing students’ communication skills. These strategies not only support the delivery of teaching material but also align with Islamic communication values that emphasize ethics, wisdom, and courtesy. Supporting factors in the development of communication skills include lecturer competence, a supportive learning environment, and the availability of learning media. Conversely, inhibiting factors include the dominance of lecture-based methods, low student self-confidence, and limited facilities and infrastructure. The conclusion of this study affirms that communication skills in Qur'an and Hadith instruction must be developed through holistic and adaptive strategies. Lecturers play a crucial role in creating a dialogic and constructive learning climate, while also serving as role models in communication. With proper communication development, students will not only gain a deeper understanding of the subject matter but also be prepared to become critical, communicative, and morally upright Muslim individuals.